2015
DOI: 10.1371/journal.pbio.1002305
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Free Energy Landscape of PKA Inhibition and Activation: A Double-Conformational Selection Model for the Tandem cAMP-Binding Domains of PKA RIα

Abstract: Protein Kinase A (PKA) is the major receptor for the cyclic adenosine monophosphate (cAMP) secondary messenger in eukaryotes. cAMP binds to two tandem cAMP-binding domains (CBD-A and -B) within the regulatory subunit of PKA (R), unleashing the activity of the catalytic subunit (C). While CBD-A in RIα is required for PKA inhibition and activation, CBD-B functions as a “gatekeeper” domain that modulates the control exerted by CBD-A. Preliminary evidence suggests that CBD-B dynamics are critical for its gatekeepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 66 publications
(76 reference statements)
6
47
0
Order By: Relevance
“…Higher flexibility occurs only in N3A:A, αB-αC:B, and a few loops. Flexibility is pronounced in the β4-β5 loop of CBD-B, consistent with high B factors of this region in 1RGS (3) and with NMR relaxation data (14). The RMSF SDs for all ABbound residues are below 0.1 Å (Fig.…”
Section: Nonreciprocal Responses In Conformational Flexibility To Campsupporting
confidence: 83%
See 2 more Smart Citations
“…Higher flexibility occurs only in N3A:A, αB-αC:B, and a few loops. Flexibility is pronounced in the β4-β5 loop of CBD-B, consistent with high B factors of this region in 1RGS (3) and with NMR relaxation data (14). The RMSF SDs for all ABbound residues are below 0.1 Å (Fig.…”
Section: Nonreciprocal Responses In Conformational Flexibility To Campsupporting
confidence: 83%
“…We thus expect that, if this interaction is eliminated, as by the W260A mutation, the allosteric pathway should be impaired. NMR experiments of Melacini and coworkers (14) have shown that the W260A mutation produces chemical shift changes in CBD-A regions, including β5-β6 and αC/αC′, that interface with CBD-B. This CSP pattern is similar to that from deleting CBD-B altogether.…”
Section: W260a Mutation Mimics Campmentioning
confidence: 83%
See 1 more Smart Citation
“…R-subunit dynamics are important for holoenzyme activation, as highlighted by the extended αB/C/N-helix in the holoenzyme in contrast to the kinked helices in the cAMP-bound R-subunits. Several studies have characterized the dynamic features of the αB/C/N-helix, including a "flipped-back" model for PKA activation (38)(39)(40). The thermodynamic properties of the 2 CNB domains are critically intertwined and sensitive to ligand binding as well as mutation of the neighbor (41).…”
Section: Resultsmentioning
confidence: 99%
“…Although this communication is straightforward in specific cases of two differing neighboring domains or heterodimers in which domains have distinct ligands (6)(7)(8), it is more elusive for the common case of symmetric homodimers. Homodimers present a challenge because it is difficult to either observe individual protomers or study states with a single ligand bound (referred to here as "lig 1 ") because of dynamic binding equilibria.…”
mentioning
confidence: 99%